The importance of biofilm contamination control for dental unit waterlines: a multicenter assessment of the microbiota diversity of biofilm in dental unit waterlines - Piaopiao Chen; Jiang Zeng; Feiruo Hong; Cong Li; Huimin Wang; Xuefen Yu (Journal of Oral Microbiology, 2024)
Background The biofilm formation in Dental Unit Waterlines (DUWLs) could become an important cause of infection during dental care, which could put immunocompromised individuals at risk of cross-infection. The aim of this study was to characterize the microbial communities of biofilms among DUWLs using high-throughput sequencing technology.Methods Twenty-nine biofilm samples were obtained from 24 dental chair units at 5 hospitals and 2 dental clinics. The genomic DNA of the samples was extracted, then 16S rDNA and ITS2 gene were amplified and sequenced. Alpha-diversity and Beta-diversity were calculated with QIIME2 and the Kruskal – Wallis H-test was adopted for statistical analysis.Results Microbial communities with a high diversity of bacteria (377 genera) and fungi (83 genera) were detected in the biofilm samples. The dominant phylum of bacteria was Proteobacteria (93.27%) and that of fungi was Basidiomycota (68.15%). Potential human pathogens were detected including 7 genera of bacteria (Pseudomonas, Stenotrophomonas, Hafnia-Obesumbacterium, Burkholderia-Caballeronia-Paraburkholderia, Ralstonia, Enterobacter, Klebsiella) and 6 genera of fungi (Malassezia, Candida, Alternaria, Cryptococcus, Rhodotorula, Rhinocladiella).Conclusions This multicenter assessment revealed the infectious risk during dental care. It emphasized the importance of biofilm control due to biofilm accumulation and multiple kinds of opportunistic pathogens in DUWLs.